Analysis of APTT Based Clot Waveform Parameters in Various Clinical Conditions – A Study at A Tertiary Care Center - Rachana Lakhe; Amit Nisal; Preeti Doshi; Ravindra Nimbargi (Universitas Nahdlatul Ulama Surabaya, 2023)
Various coagulation tests like Prothrombin Time (PT) and Activated Partial Thromboplastin Time (APTT) are estimated by automated coagulation analyzers. The newer fully automated analyzers generate clot wave forms aPTT-CWA for these parameters are derived. In this study, the objective was to analyze clot wave form characteristics morphology and its first and second derivative values in cases with abnormal APTT. ACL TOP 300 generated curves for APTT in a total 125 patients with 20 normal controls are included. First derivative, second derivative, morphology of curve: sigmoid, biphasic, prolonged pre-coagulation phase, second derivative morphology like early and late shoulder, biphasic peak, delayed deceleration were the analyzed parameters. Wave clot forms of 125 patients were included in this study. Patients (M:F - 2.2:1, mean age: 46.9 ± 20 years). A spectrum of clinical conditions was Covid (20%), liver disease (23%), polytrauma (10.4%), cardiac diseases (8.8%), sepsis/DIC (7.2%), thromboembolism (7.2%), renal diseases (6.4%), bacterial infections (4%), dengue (4%), snake bite (1.6%) and factor deficiency (1.6%). Liver and heart disease showed a significant difference in acceleration and deceleration peaks followed by sepsis, dengue, polytrauma and sepsis/DIC. Deceleration peak was prolonged in patients of Covid (p<0.05). Sepsis and liver diseases showed prolonged first derivative peak (p<0.05). CWA is very easily available on all automated coagulation analyzers. It is inexpensive with fast turn round time. Both quantitative as well as qualitative informations such as velocity, acceleration of clot formation and wave pattern details were recorded. Our study highlights importance of quantitative and qualitative CWA parameters acquired by performing APTT test for the automated analyzers.